Petrology and geochemistry of Timiskaming Group sedimentary rocks, Kirkland Lake area, Abitibi greenstone belt. - Legault, Marc Ian. (University of Ottawa (Canada), 1993)
The Timiskaming Group is a late Archaean syn-tectonic lithological unit which lies unconformably on greenstone-belt volcanic rocks and consists of an alluvial-fluvial assemblage intercalated with alkalic volcanic rocks and a turbidite assemblage. The fine-grained sedimentary rocks of the alluvial-fluvial assemblage and turbidite north unit have similar mineralogical and chemical compositions such as high SiO$\sb2$, U, Th and total rare-earth elements (REE). The turbidite south unit has high Fe$\sb2$O$\sb{3(\rm tot)}$, MgO, TiO$\sb2$, Cr and Ni. Petrographic and geochemical examinations of clasts from the alluvial-fluvial assemblage indicate that the clasts are mostly igneous rocks with minor sedimentary rocks. Four major types of igneous clasts are recognized: calc-alkaline porphyries, trachytes, trondhjemites and tholeiitic basalts. Results indicate that the turbidite south unit is the oldest unit of the Timiskaming Group and the age of sedimentation is bracketed between 2685 Ma and 2700 Ma. It was derived from an undissected arc terrane uplifted during accretion. Sources for the turbidite south unit estimated from chemical compositions of shales are 12% rhyolite, 18% komatiite and 70% andesite. The alluvial-fluvial assemblage and turbidite north unit are inferred to have been derived from a dissected island arc after accretion, but before the unroofing of K-rich intrusions, which are presently extensively exposed. A source comprising 60% calc-alkaline porphyries, 20% trachytes and 20% tholeiitic basalts is estimated for the turbidite north unit from the chemical composition of shales. The distribution of trachyte clasts in the alluvial-fluvial assemblage only close to the Lander Lake-Cadillac Fault (LLCF) suggests that displacement along the fault may have created conduits for alkaline magmas. Similar lithology of conglomerates north and south of the fault suggests that the alluvial-fluvial assemblage was deposited in a pull-apart basin after juxtaposition of two tectonic blocks along the fault between 2685 and 2677 Ma. (Abstract shortened by UMI.)
Keywords: Geology.